Salmonid Alphavirus Subtype 3 Induces Prolonged Local B Cell Responses in Atlantic Salmon (Salmo salar) After Intraperitoneal Infection - Jenberie, Shiferaw; Peñaranda, Ma. Michelle D.; Thim, Hanna L.; Styrvold, Morten Bay; Strandskog, Guro; Jørgensen, Jorunn B.; Jensen, Ingvill (Frontiers in Immunology, 2020)
B cell responses are a crucial part of the adaptive immune response to viral infection. Infection by salmonid alphavirus subtype 3 (SAV3) causes pancreas disease (PD) in Atlantic salmon (Salmo salar) and is a serious concern to the aquaculture industry. In this study, we have used intraperitoneal (IP) infection with SAV3 as a model to characterize local B cell responses in the peritoneal cavity (PerC) and systemic immune tissues (head kidney/spleen). Intraperitoneal administration of vaccines is common in Atlantic salmon and understanding more about the local PerC B cell response is fundamental. Intraperitoneal SAV3 infection clearly induced PerC B cell responses as assessed by increased frequency of IgM+ B cells and total IgM secreting cells (ASC). These PerC responses were prolonged up to nine weeks post-infection and positively correlated to the anti-SAV3 E2 and to neutralizing antibody responses in serum. For the systemic immune sites, virus-induced changes in B cell responses were more modest or decreased compared to controls in the same period. Collectively, data reported herein indicated that PerC could serve as a peripheral immunological site by providing a niche for prolonged maintenance of the ASC response in Atlantic salmon.